2020
DOI: 10.3390/molecules25215010
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Biological Activity of Berberine Chloride against Uropathogenic E. coli Strains Using Galleria mellonella as a Host Model

Abstract: Berberine is an alkaloid of the protoberberine type used in traditional oriental medicine. Its biological activities include documented antibacterial properties against a wide variety of microorganisms; nonetheless, its use against Escherichia coli strains isolated from urinary infections has not yet been widely investigated in vivo. The emergence of antimicrobial resistance requires new therapeutic approaches to ensure the continued effectiveness of antibiotics for the treatment and prevention of urinary infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…In one study, researchers used Galleria mellonella as an infection model to report, for the first time, that berberine also has certain anti-invasive activity in vitro [ 72 ]. Studies have shown that berberine inhibits DNA replication, RNA transcription, and protein biosynthesis in bacteria.…”
Section: Antibacterial Mechanisms Of Natural Alkaloidsmentioning
confidence: 99%
“…In one study, researchers used Galleria mellonella as an infection model to report, for the first time, that berberine also has certain anti-invasive activity in vitro [ 72 ]. Studies have shown that berberine inhibits DNA replication, RNA transcription, and protein biosynthesis in bacteria.…”
Section: Antibacterial Mechanisms Of Natural Alkaloidsmentioning
confidence: 99%
“…These findings were also noted in a study conducted by Petronio et al, which determined that uropathogenic Escherichia coli (UPEC) is a heterogeneous group of extra intestinal pathogenic E. coli with several virulence factors that allow these bacteria to colonize the urinary tract and resist the host's defense mechanisms. These virulence factors are distinctive and very different from those observed in other human microbial communities; among them are type 1 fimbriae and P fimbriae, which are present on the bacteria surface [50]. Poor hygiene on the insertion site was observed in most of the study participants, as there was a large build-up of secretions observed during sampling leading to CA-UTI In general, GNB causing CA-UTI among patients with IUC showed higher and moderate resistance towards antibiotics of the first (i.e., ampicillin and trimethoprimsulfamethoxazole) and second (i.e., ceftriaxone) lines of treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Berberine is an alkaloid that has been widely used as an anti-infective agent in traditional medicine. It possesses antibacterial activities against a wide range of microorganisms alone or in combination with antibiotics routinely [ 210 , 211 , 212 ].…”
Section: Preclinical and Clinical Studies On Antibacterial Effects Of Phytochemicalsmentioning
confidence: 99%
“…Galleria mellonella as an infection model was used to confirm berberine’s ability to reduce bacterial adhesion and invasion proprieties of E. coli on human bladder cells. The results indicated that increasing the surviving larvae infected with pathogens reduced circulating uropathogenic E. coli strains in larvae hemolymph [ 210 ].…”
Section: Preclinical and Clinical Studies On Antibacterial Effects Of Phytochemicalsmentioning
confidence: 99%